ANALISIS KOMUNIKASI DIGITAL LEWAT INSTAGRAM UNTUK PRODUCT BRANDING BRAND ERIGO - Satrio Putra Hartanto (Ilmu Komunikasi, 2026)
Abstract - The rapid evolution of digital technology has profoundly reshaped how companies build product branding and engage with consumers. In Indonesia, Instagram has become a key strategic platform for local brands to carry out marketing and branding communication. This study aims to analyze the digital communication strategies employed by the local brand Erigo on Instagram to develop product branding targeted at younger audiences. Using a descriptive qualitative approach, the research collects data through content observation of Erigo’s Instagram account, documentation, and a review of relevant literature. The findings indicate that Erigo strategically utilizes Instagram features—including feeds, stories, reels, and influencer collaborations—to strengthen its brand and drive audience engagement. Moreover, the consistent use of visual and narrative strategies plays a crucial role in shaping a strong, relevant brand image that resonates with its target market. The study concludes that the strategic use of Instagram serves as an effective digital communication tool for strengthening product branding, particularly for local brands operating in today’s digital era.